2014
DOI: 10.5194/acp-14-10211-2014
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal distributions of aerosol constituents and their mixing states in Antarctica during the JASE traverse

Abstract: Abstract. Measurements of aerosol number concentrations and direct aerosol sampling were conducted on continental Antarctica during the traverse of the Japanese-Swedish joint Antarctic expedition (JASE) from 14 November 2007 until 24 January 2008. Aerosol concentrations in background conditions decreased gradually with latitude in inland regions during the traverse. The lowest aerosol number concentrations were 160 L −1 in D p > 0.3 µm, and 0.5 L −1 in D p > 2 µm. In contrast, aerosol concentrations reached 32… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 80 publications
4
34
1
Order By: Relevance
“…Also, the major ions are consistent with the major salts NaCl, Na 2 SO 4 and NaNO 3 . The results are also consistent with Hara et al (2014), who seldom found ammonium salts, instead found that some of the major aerosol compositions on the same traverse route are Na 2 SO 4 and NaNO 3 . NaNO 3 is thought to be formed by (Kerminen et al, 2000) NaCl þ HNO 3 !…”
Section: Chemical Characteristics Of Soluble Particles From Coastal Tsupporting
confidence: 81%
See 4 more Smart Citations
“…Also, the major ions are consistent with the major salts NaCl, Na 2 SO 4 and NaNO 3 . The results are also consistent with Hara et al (2014), who seldom found ammonium salts, instead found that some of the major aerosol compositions on the same traverse route are Na 2 SO 4 and NaNO 3 . NaNO 3 is thought to be formed by (Kerminen et al, 2000) NaCl þ HNO 3 !…”
Section: Chemical Characteristics Of Soluble Particles From Coastal Tsupporting
confidence: 81%
“…The scatter in these ternary diagrams exceeds that from previous aerosol analyses on the same traverse route (Hara et al, 2014). Since only a limited number of particles are actually used for EDS, sample heterogeneity may have contributed to the observed scatter.…”
Section: Sea-salt Modification Of Single Particles From Coastal To Inmentioning
confidence: 48%
See 3 more Smart Citations